PERAN HUKUM ADAT DALAM PELESTARIAN NILAI-NILAI KEARIFAN LOKAL KAMPUNG ADAT CIRENDEU DAN TANTANGANNYA DI ERA MODERN - Hutabarat, Masna Bonita; Nabilah, Nazhifatun Zulfa; Anggraeni, Leni; Sopianingsih, Pitria (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
This study analyzes the role of customary law in preserving local wisdom and the challenges faced in the modern era through a case study of the Cireundeu Traditional Village in Cimahi. Customary law is manifested through the pamali system, traditional environmental zoning, and marriage regulations that function as social control and cultural guidance. A qualitative case study approach was employed using interviews, observations, and documentation. Findings indicate that customary law plays a crucial role in shaping cultural identity, maintaining social harmony, and supporting environmental sustainability. However, modernization, digital technology, and national regulations present significant challenges, especially for younger generations living in a rapidly changing information landscape. Despite these challenges, the community adapts through educational efforts, logical explanations of adat rules, and the use of technology for cultural preservation. The study concludes that strong collaboration between the government and indigenous communities is essential to ensure the sustainability and legal protection of customary law.